WRKY13 acts in stem development in Arabidopsis thaliana. (July 2015) - Li, Wei; Tian, Zhaoxia; Yu, Diqiu
Highlights: Mutation of WRKY13 causes weaker stem phenotype. Mutation of WRKY13 causes reduced sclerenchyma development and altered lignin synthesis. Several secondary cell wall synthesis genes were affected in wrky13 mutants and NST2 is the direct downstream gene of WRKY13. Abstract: Stems are important for plants to grow erectly. In stems, sclerenchyma cells must develop secondary cell walls to provide plants with physical support. The secondary cell walls are mainly composed of lignin, xylan and cellulose. Deficiency of overall stem development could cause weakened stems. Here we prove that WRKY13 acts in stem development. The wrky13 mutants take on a weaker stem phenotype. The number of sclerenchyma cells, stem diameter and the number of vascular bundles were reduced in wrky13 mutants. Lignin-synthesis-related genes were repressed in wrky13 mutants. Chromatin immunoprecipitation assays proved that WRKY13 could directly bind to the promoter of NST2 . Taken together, we proposed that WRKY13 affected the overall development of stem. Identification of the role of WRKY13 may help to resolve agricultural problems caused by weaker stems.